2018
DOI: 10.20517/2573-0002.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of elevated mast cell and micro-vessel densities with lymph node metastasis in oral squamous cell carcinoma

Abstract: How to cite this article: Nakandala K, Suraweera A, Jayasooriya P. Correlation of elevated mast cell and micro-vessel densities with lymph node metastasis in oral squamous cell carcinoma. AbstractAim: Oral squamous cell carcinoma (OSCC) is a major health problem in Sri Lanka. Tumor-node-metastasis (TNM) staging system is the tool which is used to determine the extent of surgery in patients with OSCC. However, some patients may receive over-treatment with TNM staging. Mast cells can be found in the oral mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…This was found to be highly statistically significant and consistent with the results by Sathyakumar 23 and Hegde et al 26 In OSCC, our results showed a mild positive correlation between MCD and MVD that was not statistically significant, consistent with the results of Hegde et al 26 and Nakandala et al 11 The mild positive correlation may be due to the failure of migration of mast cells, or factors other than mast cells probably involved in tumor angiogenesis. 11 In other words, initially, mast cells might infiltrate cancerous tissue to suppress tumor activities, but, once invasion occurs, their cytotoxic effects are nullified, thereby enhancing tumor progression rather than supporting angiogenesis. 26 This mast cell-mediated cytotoxicity was reported when the mast cell:tumor ratios are greater than 20:1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was found to be highly statistically significant and consistent with the results by Sathyakumar 23 and Hegde et al 26 In OSCC, our results showed a mild positive correlation between MCD and MVD that was not statistically significant, consistent with the results of Hegde et al 26 and Nakandala et al 11 The mild positive correlation may be due to the failure of migration of mast cells, or factors other than mast cells probably involved in tumor angiogenesis. 11 In other words, initially, mast cells might infiltrate cancerous tissue to suppress tumor activities, but, once invasion occurs, their cytotoxic effects are nullified, thereby enhancing tumor progression rather than supporting angiogenesis. 26 This mast cell-mediated cytotoxicity was reported when the mast cell:tumor ratios are greater than 20:1.…”
Section: Discussionsupporting
confidence: 92%
“…9 Many studies have proved that mast cells accumulate in many angiogenesis-dependent situations, both in physiological and pathological situations like rheumatoid arthritis, wound healing, ovulation, and hemangioma, 10 and around the tumor margins, as well as releasing pro-angiogenic and angiogenic factors which play a major role in tumor progression. 11,12 Though there are many studies associating mast cells and angiogenesis in many oral lesions (squamous cell carcinoma/dysplasia/lichen planus separately, or combining any of these lesions) (Table 1), to the best of our knowledge none of the studies has correlated all these lesions together. No studies have correlated these two factors in lichen planus so far.…”
Section: Introductionmentioning
confidence: 99%